ONE-DIMENSIONAL MOTION EXPERIMENTS AND DATA PROCESSING USING THE RASPBERRY PI AND PYTHON - soni prayogi (Journal of Teaching and Learning Physics, 2023)
In this study, we try to propose a simple electronic computational experiment of one-dimensional motion, which combines physics and computer science. Our experimental setup is based on the Raspberry Pi3 model B with the Raspbian operating system. The ultrasonic proximity sensor is the HC-SR04, which can be powered using the +5V DC output of the Raspberry Pi. An ultrasonic proximity sensor is used to obtain the position of a selected target along a linear path, with a Raspberry Pi and simple Python code. Another simple script is proposed to calculate velocity and acceleration and for a graphical presentation of the results. Our results show that motion can be qualitatively and quantitatively defined, and the experiment is suitable for undergraduate students or for younger students